2010
DOI: 10.1128/jcm.02075-09
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Sequencing in Routine Identification of Anaerobic Bacteria Isolated from Blood Cultures

Abstract: A comparison between conventional identification and 16S rRNA gene sequencing of anaerobic bacteria isolated from blood cultures in a routine setting was performed (n ‫؍‬ 127). With sequencing, 89% were identified to the species level, versus 52% with conventional identification. The times for identification were 1.5 days and 2.8 days, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Since November 2007, 16S rRNA gene sequencing (MicroSeq 500 system; Perkin-Elmer, Applied Biosystems Division, Foster City, CA) has been applied to pure culture material (originating from blood cultures) from solid media as soon as anaerobic bacteria, including Lactobacillus spp. and Actinomyces spp., were suspected (8). From November 2008, this strategy has also included pure culture material from other sterile body sites (e.g., the central nervous system, pleura, bones, and joints) and suspected Fusobacterium spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since November 2007, 16S rRNA gene sequencing (MicroSeq 500 system; Perkin-Elmer, Applied Biosystems Division, Foster City, CA) has been applied to pure culture material (originating from blood cultures) from solid media as soon as anaerobic bacteria, including Lactobacillus spp. and Actinomyces spp., were suspected (8). From November 2008, this strategy has also included pure culture material from other sterile body sites (e.g., the central nervous system, pleura, bones, and joints) and suspected Fusobacterium spp.…”
mentioning
confidence: 99%
“…Identification by 16S rRNA gene sequencing was chosen as the "gold standard" in this study, as it has been shown to be an excellent method for the identification of anaerobic bacteria (8). All isolates identified to the species level with a Ն99% match by 16S rRNA gene sequencing, according to CLSI guideline MM18-A (6), from the period November 2007 to October 2010, were included in the study (only one isolate of the same species per patient).…”
mentioning
confidence: 99%
“…The reasons for this are probably multifactorial. First, regular use of 16S rRNA partial gene sequencing significantly expands the number of anaerobic organisms that can be accurately identified (10,16). It is also well recognized that Leptotrichia are not reliably identified by a commonly used phenotypic identification system (RapID ANA II; Remel, Lenexa, KS) (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…A previously described 16S rRNA gene PCR targeting an 817-base-pair fragment was used [12][13][14]. Sequencing results were interpreted using the CLSI (Clinical and Laboratory Standards Institute) guideline MM18-A "Interpretive Criteria for Identifi cation of Bacteria and Fungi by DNA Target Sequencing; Approved Guideline" [15] as detailed [16]. MALDI-TOF-MS analysis was performed using a Shimadzu/Kratos "AXIMA Assurance" MALDI-TOF mass spectrometer (Shimadzu Germany Ltd., Duisburg, Germany) as described [14] with a minor modifi cation.…”
Section: Assessment Of Isolated Strainsmentioning
confidence: 99%